Structural analysis of sandwich thin-walled hollow cylindrical tubes with aluminum foam filler subjected to low velocity axial load using numerical simulation - Ly, Hung Anh (ASEAN engineering journal)
Impact sefety and weigh-saving are two important criteria for energy-absorbing structures in train, car and aircraft design. Innovations in light-weight material such as metallic cellular material, aluminum foam have developed significantly; it opens many researches to enhance capability of energy absorber. Research on structure of sandwich thin-walled cylindrical tubes with aluminum foam filler has been conducted much; however, the number of researches focusing on sandwich thin-walled hollow cylindrical tubes with aluminum foam filler is limited. This paper presents numerical analyses of sandwich thin-walled hollow cylindrical tubes with aluminum foam filler subjected to low velocity axial loading using a non-linear finite element method. The objective is to predict and compare the behavior of these structures in absorbing energy.